Reporte de un caso: tratamiento farmacológico del Embarazo Ectópico: Report of a case: pharmacological treatment of Ectopic Pregnancy (La U Investiga, 2019)
An ectopic pregnancy is defined when the fertilized oocyte implants outside the endometrial cavity. The incidence has increased in recent decades to reach 1-2%. Currently, the rupture of ectopic pregnancy continues to be an important cause of pregnancy-related morbidity and mortality, so their study is still relevant. The availability of highly sensitive methods of detecting gonadotrophins and the use of high-resolution transvaginal ultrasonography have made it possible to diagnose Ectopic Pregnancy earlier, allowing the use of less aggressive treatments such as the use of metotrexate. The case report presented in an adult patient of childbearing age, who attended the Gynecological Emergencies service of the General Hospital of Ibarra and received medical treatment with Metotrexate.Conclusions: Metotrexate treatment has shown very good results with high success rates, allowing preserving maternal fertility and involving lower costs to the health system.
Keywords: Ectopic Pregnancy; pharmacological treatment; Metotrexato